O papel da cultura brasileira frente à obesidade infantil durante as últimas três décadas - Nathalye Emanuelle Souza (Residência Pediátrica)
Childhood obesity can affect health in adulthood in several ways. First, studies have shown that obese children are more likely to become obese adults. This significantly increases the risk of developing chronic diseases such as diabetes, hypertension, heart disease, cancer and other conditions that can negatively impact quality of life. This work seeks to bring reflections on environmental and cultural changes in terms of habits, which may have contributed to the increase in obesity in the Brazilian population, through advertising, as well as typical foods and childrens routine before the COVID-19 pandemic.